The Routledge international handbook on fear of crime - Lee, Murray; Mythen, Gabe (Routledge international handbooks, 2018)
Introduction -- Histories of fear of crime -- Fear of crime before "fear of crime" / Barry Godfrey -- "Hot under the collar" : the garrotting moral panic of the 1860's / Chas Critcher -- The discovery of fear of crime in the U.K. / Mike Hough -- The ebbs and flows of anxiety : how emotional responses to crime and disorder influenced social policy in the U.K. in the twenty-first century / Emily Gray -- Mediating fear of crime -- Fear the monster : racialised violence, sovereign power and the thin blue line / Travis Linnemann and Corina Medley -- After the culture of fear : fear of crime in the United States half a century on / Jonathan Simon -- Fear 2.0 : worry about cybercrime in England and Wales / Ian Brunton-Smith -- Beyond moral panic : young people and fear of crime / Kelly Richards and Murray Lee -- Nothing to fear but fear itself? : liquid provocations for new media and fear of crime / Jamie K. Wardman -- Methodologies and conceptual debates -- A construal-level approach to the fear of crime / Ioanna Gusetti -- Qualifying fear of crime : multi-methods approaches / Murray Lee and Justin R. Ellis -- Visual methods in research on fear of crime : a critical assessment / Gabry Vanderveen -- The perils of "uncertainty" for fear of crime research in the twenty-first century / Will McGowan -- Dissecting and Stratifying Fear of Crime -- Crime and the fear of Muslims / Scott Poynting -- Gender, violence and fear of crime : women as fearing subjects? / Sandra Walklate -- Discovering "the enemy within" : the state, fear and criminology / Karen Evans -- Law, regulation and policing the fear of crime -- In the eye of the (motivated) beholder : towards a motivated cognition perspective on disorder perceptions / Jonathan Jackson, Ben Bradford, Ian Brunton-Smith and Emily Gray -- Countering the fears of terrorism : policing and community relations / Basia Spalek and Tracey Davanna -- Do police officers fear crime in the same way as the population? : results of a local police survey on insecurity and fear of crime in Switzerland / Christine Burkhardt, Natalia Delgrande and Partice Villettaz -- Policing, performance indicators and fear of crime / Alyce McGovern -- Curating risk, selling safety? : fear of crime, responsibilisation and the surveillance school economy / Emmeline Taylor -- Contexts and geographies of fear of crime -- Removing fear of crime : the role of regulation in creating safer spaces for sex workers / Teela Sanders and Lynzi Armstrong -- Fear and insecurity in Latin America / Lucía Dammert and Felipe Salazar -- Fear of crime and overall anxieties in rural areas : the case of Sweden / Vania Ceccato -- Additive and synergistic perceived risk of crime : a multilevel longitudinal study in Peru / Wilson Hernández -- Punitive populism and fear of crime in Central America / Sebastian Huhn -- Fear of crime research in China / Jianhong Liu and Shan Cui -- Connecting fear of crime : new approaches and ways forward -- How to break a rape culture : gendered fear of crime and the myth of the stranger-rapist / Alex Fanghangel -- Becoming feared : fashioning and projecting the violent self / Mark Halsey -- The fear drop / Marnix Eysnick Smeets and Pim Foekens -- "Hyphenated fears" and "camouflaged" responses : fear of crime, war and militarism / Ross McGarry -- Conclusion